Reactively Magnetron Sputter-Deposited Ti (C,N) Nanocomposite Thin Films: Composition and Thermal Stability - Fouad, Osama A.; Lin, Hong-Ying; Shah, S. Ismat (Journal of Coating Science and Technology, 2018)
Titanium carbonitride thin films were grown by reactive magnetron sputtering deposition of titanium carbide target in Ar/N2 gas mixture on p-type silicon (100) substrates. With the increase of sputtering power up to 125W, the deposition rate and films thickness reached a maximum of 14nm/min and 430nm, respectively. A thick film of about 2200nm could be deposited for 120 min at the optimum deposition pressure of 20mTorr. Cathode current decreased from about 290mA to reach a value of about 235mA as the N2 flow percentage increased from 0 to 100%. X-ray diffraction analyses of the deposited films confirmed the formation of titanium carbide and carbonitride layers as the nitrogen gas concentrations in the process gas were increased. SEM image of the deposited titanium carbonitride thin film for 5 min deposition time showed that the film started to grow as tiny particles of size as low as about 140nm, which in later stage coalesced together to form bigger grains and finally a continuous film. The deposited film shows good thermal stability upon annealing in air and in vacuum at 700oC for 2 hours.